Efektivitas Pelaksanaan Program Jaminan Kesehatan Nasional Dalam Rangka Meningkatkan Pelayanan Kesehatan Bagi Masyarakat Kurang Mampu di Puskesmas Kediri III - Ni Wayan Idayani (Jurnal Widya Mahavira, 2026)
This study aims to determine the effectiveness of the National Health Insurance (JKN) program in improving health services for underprivileged communities at the Kediri III Community Health Center, Beraban Village, Kediri District, Tabanan Regency. The study used a descriptive qualitative approach with a phenomenological approach. Data collection techniques included observation and interviews with informants from community health center staff and community JKN users. The results indicate that the implementation of the JKN program at the Kediri III Community Health Center has been quite effective. This can be seen from four main indicators: (1) Available and sustainable - services are fast and the process for JKN card users is simplified; (2) Acceptable and appropriate - the community is satisfied with the services provided; (3) Easily accessible - strategic location, adequate facilities, and widespread socialization; (4) Quality - the community feels the program's results, experiences no obstacles, and the program is well-targeted to underprivileged communities.